Perspectives of adult advanced pre-dialysis chronic kidney disease patients about kidney replacement therapy in three referral hospitals in Rwanda - Gloria Shumbusho; Darlene L. Nyenyeri; Jules Kabahizi; Darius Uwiragiye; Oswald Habyarimana; Gad Binayisa; Alice Nyirangirimana; Emile Twagirumukiza; Kara L. Neil; Negussie Deyessa; Alan Leichtman; Janvier Murayire; et al. (BMC Nephrology)
Abstract Background Limited access to kidney replacement therapy (KRT) in Rwanda results from financial constraints, geographic challenges, a shortage of nephrologists and equipment, as well as low public awareness. We aimed to identify the factors contributing to patients’ decisions regarding KRT and understand their perspectives on KRT, including their understanding, attitudes, and expectations. Methods A cross-sectional mixed method design was conducted between May 2023 and March 2024, involving 180 chronic kidney disease (CKD) adult patients (> 18 years old) with an estimated GFR < 30 ml/min/1.73 m². It was conducted at outpatient nephrology clinics at King Faisal Hospital-Rwanda, Kigali University Teaching Hospital, and Rwanda Military Hospital. Quantitative data from hospital registries were analyzed in Stata SE 17.0, employing descriptive, bivariate, and multinomial techniques to determine factors associated with KRT modality choice. Additionally, 15 participants were conveniently selected for interviews and analysis of transcripted records were conducted using ATLAS.ti. Results The mean age was 52.2 [SD = 13.9] years, with a higher representation of males. Two-thirds of the participants had end-stage kidney disease (kidney failure) with a mean eGFR of 14.64 ml/min/1.73m2. Most participants (72.1%) were primarily informed by doctors about KRT and 81.5% were willing to undergo KRT. There was a marked preference for kidney transplantation (74.4%) over dialysis, however, 45.6% of them were reluctant to ask for a kidney donation. Multinomial analysis revealed that patients with previous nephrology visits were more likely to opt for kidney transplantation (aOR = 6.19, 95% CI: 1.99–19.23, p = 0.002). Interview revealed varying levels of knowledge about KRT, significant psychological impacts including feelings of isolation and treatment anxiety, and universal preference for kidney transplantation despite concerns about donor availability and costs. Conclusion The findings revealed that prior nephrology visits significantly influenced treatment choices. Healthcare providers served as key information sources, while financial constraints and limited knowledge of CKD progression and management emerged as major barriers to optimal care. The findings indicate the need for establishing pre-dialysis clinics for improved information access and patient support. Clinical trial number Not applicable.